Pollen–pistil interactions in reproductive interference: comparisons of heterospecific pollen tube growth from alien species between two native Taraxacum species. (20th September 2013) - Nishida, Sachiko; Kanaoka, Masahiro M.; Hashimoto, Keisuke; Takakura, Koh‐Ichi; Nishida, Takayoshi; Kudo, Gaku
Summary Reproductive interference (RI), any negative interspecific interaction during the reproductive process, has been gaining increasing attention due to its potential explanatory power for the mutually exclusive distribution of closely related species. RI in plants may occur during any of three stages: pollen transfer, pollen–pistil interactions or hybridization. Pollen–pistil interactions may be especially important as most studies of RI have suggested the involvement at this stage. Details of these interactions are required to fully explore RI and are especially relevant in considering the impact of RI in the field. We present a plausible explanation of how RI functions in the pollen–pistil interaction stage using two Japanese native dandelions, Taraxacum japonicum and Taraxacum longeappendiculatum, of which only the former is vulnerable to RI from an alien congener, Taraxacum officinale. We conducted a series of hand pollinations in these native dandelions and compared pollen tube behaviour to examine differences associated with vulnerability and imperviousness to RI from the alien. The two native dandelions differed in terms of the absence/presence of pollen tube elongation after heterospecific pollination (pollination with only T. officinale): pollen tubes grew through the ovaries of the vulnerable T. japonicum, but not through those of the impervious T. longeappendiculatum. In vitro hand pollination verified that the alien pollen tubes could extend into the ovaries of T. japonicum. Our results show that RI from the alien dandelion consumed ovules by heterospecific pollen deposition. The pistils of the impervious native species could prevent growth of the alien pollen tubes, thereby sparing the ovules for fertilization by conspecific pollen. The pistils of the vulnerable species lacked interspecific incompatibility against the alien, and thus, the alien pollen tube entered the ovary, eliminating an opportunity for conspecific pollen fertilization. This consumption of ovules by heterospecific pollen tubes would cause a seed set failure, leading to reduced abundance and a further exertion of RI in the next generation, which explains displacement of the vulnerable species by the alien in the field.